Peran Kompetensi Kebahasaan Guru dalam Pengembangan Sikap Bahasa dan Karakter Anak Usia Dini - Setyowati, Titik; Nugrahani, Farida; Nurnaningsih, Nurnaningsih (Jayapangus Press, 2025)
This study aims to describe the role and optimization of teachers’ linguistic competence in shaping and developing language attitudes and character among early childhood learners. The data were collected from teachers’ spoken interactions with children during learning activities, transcripts of in-depth interviews with teachers and principals, classroom observation notes, and lesson plans and teaching materials. The informants were selected using purposive sampling. Data validity was ensured through source and technique triangulation, while data analysis employed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The results show that teachers’ linguistic competence plays an essential role in shaping children’s language attitudes and character, particularly by using language that instills politeness, discipline, and mutual respect. Effective linguistic competence also supports character development through appropriate word choice, tone, and responses that foster positive communication, respect, and self-confidence. The optimization of teachers’ linguistic competence is supported by continuous professional training, a conducive school environment, and principal support that strengthens teachers’ ability to use language effectively in early childhood education.